WITHDRAWN: Modelling and Simulation of 4 DOF Robotic Arm for an Automated Roselle Tea Processing Plant Using Solidwoks and Matlab Simulik. Issue 2 (December 2017) - Adeyeri, M.K.; Ayodeji, S.P.; Olasanoye, O.
Abstract : This article has been withdrawn: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy ). This article has been withdrawn at the request of the editor and publisher. The publisher regrets that an error occurred which led to the premature publication of this paper. This error bears no reflection on the article or its authors. The publisher apologizes to the authors and the readers for this unfortunate error.